Research on the Process Optimization and Water Retention of Curdlan Gel Emulsified Sausage - Shang, Shuqi; Liu, Wendong; Xing, Yanxia; Liu, Sheng; Chang, Guifang; Yu, Yang; Cao, Zhenling; Zhou, Ying; Li, Bo; Song, Yue; Hou, Wenbo; Zhu, He; et al. (International Journal of Natural Resources and Environmental Studies, 2024)
In the production of emulsified sausage, 0.4%, 0.6%, 1%, 1.4% and 1.6% can be added to the curdlan gel No. 1 and No. 2, respectivelyIn order to improve the water retention of beef emulsified sausage, the effect of different amounts of curdlan gel on the cooking loss of beef emulsified sausage was explored. Curdlan gum is a class of gel polysaccharides produced by microorganisms, which can improve the water retention and firmness of products at a relatively low cost. It is widely used in the food industry and can greatly improve the taste, appearance and texture of products. In this experiment, curdlan gel was added to emulsified beef sausages, and the effects of curdlan gel on the water retention of emulsified beef sausages were studied by the indicators of cooking loss rate and centrifugal loss rate, and the process was optimized by single factor experiment and orthogonal test. The experimental results showed that the optimal process for preparing emulsified sausage was as follows: marinating time 120 min, chopping and mixing water 10%, and cooking time 45 min. The best sensory score of 86.7 was obtained for the preparation of emulsified sausage by this process. The addition of curdlan gel 1 and 2 could significantly reduce the cooking loss of beef emulsified sausage (P<0.05) and improve the water retention of emulsified sausage. The lowest cooking loss rate of 15.5% and 6.53% were found to be 15.5% and 6.53% respectively when 1.4% was added, and the lowest cooking loss rate was 13.82% and 3.7% for 1.4% and 3.7% respectively. The optimal addition amount of 2 is 1.4%, and according to the comparative analysis of curdlan gel No. 1 and No. 2, the water retention of curdlan gel No. 2 is higher than that of curdlan gel No. 1, which provides a certain reference for enterprises to produce beef emulsified sausage.